Addiction: an underestimated problem in psoriasis health care. (31st March 2017) - Zink, A.; Herrmann, M.; Fischer, T.; Lauffer, F.; Garzorz‐Stark, N.; Böhner, A.; Spinner, C.D.; Biedermann, T.; Eyerich, K.
Abstract: Background: Psoriasis is a disease of enormous socio‐economic impact. Despite approval of numerous highly efficient and costly therapies, a minor proportion of severely affected patients actually receives sufficient treatment. Objective: To investigate whether addictions are associated with psoriasis and to develop evidence‐based recommendations for dermatologists in their daily clinical practice in order to improve medical assessment of psoriasis and patients' quality of life. Patients and Methods: Psoriasis patients at the University Department of Dermatology were asked to fill out a paper‐based self‐reported anonymous questionnaire with 92 questions of validated screening tests for the six most common addictions in Germany (alcohol, nicotine, drugs and illegal drugs, gambling, food). Body weight and height as well as current Psoriasis Area and Severity Index (PASI) were documented as well. Results: Between October 2015 and February 2016, 102 patients (65 males, 37 females; mean age 49.7 years (SD 13.4), range 18–83 years) participated in the study. Fifty‐seven of the 102 patients showed addictive behaviour. Of these, 23.8% were high‐risk drinkers, 41% regular smokers, 11% at risk of drug abuse, 4.1% at risk of food dependency and 19% compulsive gamblers. Compared with the general population, these results are significantly higher for alcohol abuse ( P < 0.005), nicotine ( P < 0.001) and gambling ( P < 0.001). Body mass index was significantly higher in the study population ( P < 0.001). Conclusion: Addictions and gambling are more prevalent in patients with psoriasis compared with the general population. Respective screening measures are recommended in daily practice for doctors treating psoriasis patients, and PeakPASI is suggested as a score to document patients' lifetime highest PASI. Parallel to new drug approvals and even more detailed insights into the pathomechanism of psoriasis, public health strategies and interdisciplinary approaches are essential for a general sustained psoriasis treatment.